A survey on the role of Internet of Things for adopting and promoting Agriculture 4.0. (1st August 2021) - Raj, Meghna; Gupta, Shashank; Chamola, Vinay; Elhence, Anubhav; Garg, Tanya; Atiquzzaman, Mohammed; Niyato, Dusit
Abstract: There is a rapid increase in the adoption of emerging technologies like the Internet of Things (IoT), Unmanned Aerial Vehicles (UAV), Internet of Underground Things (IoUT), Data analytics in the agriculture domain to meet the increased food demand to cater to the increasing population. Agriculture 4.0 is set to revolutionize agriculture productivity by using Precision Agriculture (PA), IoT, UAVs, IoUT, and other technologies to increase agriculture produce for growing demographics while addressing various farm-related issues. This survey provides a comprehensive overview of how multiple technologies such as IoT, UAVs, IoUT, Big Data Analytics, Deep Learning Techniques, and Machine Learning methods can be used to manage various farm-related operations. For each of these technologies, a detailed review is done on how the technology is being used in Agriculture 4.0. These discussions include an overview of relevant technologies, their use cases, existing case studies, and research works that demonstrate the use of these technologies in Agriculture 4.0. This paper also highlights the various future research gaps in the adoption of these technologies in Agriculture 4.0.